2020
DOI: 10.5620/eaht.e2020001
|View full text |Cite
|
Sign up to set email alerts
|

Lead acetate-induced neurodegenerative changes in the dorsolateral prefrontal cortex of mice: the role of Vitexin

Abstract: This study was aimed at investigating the neuroprotective effect of Vitexin against lead (Pb) induced neurodegenerative changes in the dorsolateral prefrontal cortex (DLPFC) and working memory in mice. Thirty-two adolescent male albino mice were divided into four groups (n=8). Control group received 0.2 mL of normal saline; Pb group received 100 mg/kg of Pb acetate for 14 days, Vitexin group received 1mg/kg of Vitexin for 14 days, and Pb+Vitexin group received 100 mg/kg of Pb acetate and 1 mgkg of Vitexin for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Lead acetate (abbreviated hereafter as PbAc) has been described as a neurotoxic chemical with neurodegenerative characteristics where it has been linked to CNS-related disorders . Moreover, studies suggest that PbAc intoxication can cause cellular damage via free radicals, followed by alteration in lipid metabolism, increased lipid peroxidation markers like malondialdehyde (MDA), and reduced cellular antioxidants including total antioxidant capacity (TAC) and, especially, thiol-containing compounds like glutathione (GSH). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead acetate (abbreviated hereafter as PbAc) has been described as a neurotoxic chemical with neurodegenerative characteristics where it has been linked to CNS-related disorders . Moreover, studies suggest that PbAc intoxication can cause cellular damage via free radicals, followed by alteration in lipid metabolism, increased lipid peroxidation markers like malondialdehyde (MDA), and reduced cellular antioxidants including total antioxidant capacity (TAC) and, especially, thiol-containing compounds like glutathione (GSH). , …”
Section: Resultsmentioning
confidence: 99%
“…28 Moreover, studies suggest that PbAc intoxication can cause cellular damage via free radicals, followed by alteration in lipid metabolism, increased lipid peroxidation markers like malondialdehyde (MDA), and reduced cellular antioxidants including total antioxidant capacity (TAC) and, especially, thiol-containing compounds like glutathione (GSH). 29,30 The capacity of 5e to counteract the effect of PbAc-induced oxidative stress was assessed in comparison to the reference drug rivastigmine, and the results are displayed in Figure 2. PbAc administration to experimental rats has led to increased levels of lipid peroxidation in their brain tissue (P < 0.001), thus mimicking the oxidative stress witnessed in AD brain.…”
Section: Effect Of 5e On the Level Of Induced Oxidative Stress Marker...mentioning
confidence: 99%
“…The primary constituents of apigenin flavones are glycosylated apigenin, vitexin, apiin, isovitexin and rhoifolin ( 24 ). Vitexin, c-glycosylated apigenin is now gaining considerable attention from researchers as a result of its multi-modal mechanisms of action and diverse biological advantages in different disease conditions, including neurodegenerative diseases ( 25 ). Extensive literature search has revealed that most of the reviews discussed the neuroprotective effects of general flavonoids in neurodegenerative diseases ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress injury and neuroinflammation are the major pathogenic events associated with neuronal loss in virtually all the disorders linked to the neurons, such as seizure and epilepsy ( 86 , 87 ), retinal damage ( 88 ), hypoxic-ischaemic injury ( 89 ), depression ( 90 ), cognitive dysfunction ( 91 , 92 ), sleep disorders ( 93 ) and neurodegenerative diseases ( 25 , 94 ), among others. Vitexin can attenuate ROS release in neuron disorders by activating the antioxidant response protein Nrf2, which, in turn, upregulates the activities of antioxidant enzymes ( 89 , 94 ).…”
Section: Introductionmentioning
confidence: 99%